2023
DOI: 10.3390/su152015105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Audio-Visual Environmental Factors on Emotion Perception of Campus Walking Spaces in Northeastern China

Yuyao Ma,
Jun Zhang,
Xudong Yang

Abstract: In the context of urban sustainable development and the creation of pedestrian-friendly campus environments, optimizing campus walking spaces has emerged as a central focus in urban planning research. Presently, research in pedestrian environments predominantly adopts a macroscopic perspective, offering limited insights into pedestrians’ subjective experiences and emotional perceptions at a micro level. Therefore, this study conducted on-site experiments in 21 walking spaces across three campuses, utilizing im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…We developed an approach for mapping pedestrian walking behavior on the streets of the University of Moratuwa and its vicinity. Campus walking areas are prioritized in urban sustainable development and developing pedestrian-friendly surroundings [ 2 ]. Given the nature of the experiment, this study examined walking behavior at the University of Moratuwa and its surrounds, as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed an approach for mapping pedestrian walking behavior on the streets of the University of Moratuwa and its vicinity. Campus walking areas are prioritized in urban sustainable development and developing pedestrian-friendly surroundings [ 2 ]. Given the nature of the experiment, this study examined walking behavior at the University of Moratuwa and its surrounds, as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Investigating pedestrian behavior and improving walking space in streets are becoming increasingly crucial considering the proven benefits to health, sustainability, and the development of safer pedestrian-friendly areas [ 1 , 2 ]. Consequently, an increasing amount of research has been carried out examining the relationship between the urban environment and individuals’ behavior on streets [ 3 ].…”
Section: Introductionmentioning
confidence: 99%